Comparison of Disability-Adjusted Life Years (DALYs) and Economic Burden on People With Drug-Susceptible Tuberculosis and Multidrug-Resistant Tuberculosis in Korea - Lee, SeungCheor; Kim, Moon Jung; Lee, Seung Heon; Kim, Hae-Young; Kim, Hee-Sun; Oh, In-Hwan (Frontiers in Public Health, 2022)
In the future, tuberculosis (TB) will place a heavy burden on the aging population in Korea. To prepare for this crisis, it is important to analyze the disease burden trend of drug-susceptible tuberculosis (DS-TB) and multidrug-resistant tuberculosis (MDR-TB). Measuring disability-adjusted life years (DALYs) and economic burden on MDR-TB patients can help reduce the incidence of TB. Accordingly, in this study, we measured the DALYs and economic burden on DS-TB and MDR-TB patients in 2014–2017 using a combination of National Health Insurance claims data, Annual Report on the Notified TB data, and Statistics Korea’s mortality data. The incidence-based DALY approach implemented involved the summation of years of life lost and years lived with disability. For measuring economic burden, direct and indirect costs incurred by patients were totaled. From 2014 to 2017, DALYs per 100,000 people with DS-TB were 56, 49, 46, and 40, respectively, and DALYs per 100,000 people with MDR-TB were 3, 2, 2, and 2, respectively. The economic burden for the DS-TB population from 2014 to 2017 was $143.89 million, $136.36 million, $122.85 million, and $116.62 million, respectively, while that for MDR-TB was $413.44 million, $380.25 million, $376.46 million and $408.14 million, respectively. The results showed a decreasing trend in DALYs and economic burden for DS-TB, whereas MDR-TB was still found to be burdensome without a specific trend. With respect to age, the economic burden for both DS-TB and MDR-TB was higher among men than among women till ≤ 79 years. Conversely, the economic burden for women aged ≥ 80 years was higher as compared to their male counterparts. In conclusion, the incidence and spread of TB in all areas of society must be suppressed through intensive management of MDR-TB in the older population. We hope that the national TB management project will proceed efficiently when the infectious disease management system is biased to one side due to the COVID-19 pandemic.